The power of sacred, basis of regional construction - Aldana Rivera, Susana (2019)
This article aims to reflect on historical vitality of a particular frontier area, between Loja and Huancabamba, two national states with a quite white population, with few Indians, almost without Creoles, with a border characterized different because it is translucent by its sacral symbolic movement. We reflects on the conversion of a sacred space into an economic space, its exploitation and use in accordance with kingdom interests, part of the Spanish empire. It analyzes how limits are already established and assumed, locally suffers from the pressures of trade, that were humanly established by long-standing ties and socio-economic changes that prepare the way to the republic.